Dysbindin Deficiency Modifies the Expression of GABA Neuron and Ion Permeation Transcripts in the Developing Hippocampus - Larimore, Jennifer; Zlatic, Stephanie A.; Arnold, Miranda; Singleton, Kaela S.; Cross, Rebecca; Rudolph, Hannah; Bruegge, Martha V.; Sweetman, Andrea; Garza, Cecilia; Whisnant, Eli; Faundez, Victor (Frontiers in Genetics, 2017)
The neurodevelopmental factor dysbindin is required for synapse function and GABA interneuron development. Dysbindin protein levels are reduced in the hippocampus of schizophrenia patients. Mouse dysbindin genetic defects and other mouse models of neurodevelopmental disorders share defective GABAergic neurotransmission and, in several instances, a loss of parvalbumin-positive interneuron phenotypes. This suggests that mechanisms downstream of dysbindin deficiency, such as those affecting GABA interneurons, could inform pathways contributing to or ameliorating diverse neurodevelopmental disorders. Here we define the transcriptome of developing wild type and dysbindin null Bloc1s8sdy/sdy mouse hippocampus in order to identify mechanisms downstream dysbindin defects. The dysbindin mutant transcriptome revealed previously reported GABA parvalbumin interneuron defects. However, the Bloc1s8sdy/sdy transcriptome additionally uncovered changes in the expression of molecules controlling cellular excitability such as the cation-chloride cotransporters NKCC1, KCC2, and NCKX2 as well as the potassium channel subunits Kcne2 and Kcnj13. Our results suggest that dysbindin deficiency phenotypes, such as GABAergic defects, are modulated by the expression of molecules controlling the magnitude and cadence of neuronal excitability.